GE_GERICHTE P/10151/2014 vom 14. November 2014 - GE Cour de justice (2014)
CONTRAINTE(DROIT PÉNAL); BANQUE; ÉVASION FISCALE; APPLICATION DU DROIT; DROIT ÉTRANGER; PROCÉDURE CIVILE | CPP.310; CP.181; LB.3